AnarcoAracnoAnacroArcano Tomás Saraceno - Falcone, Paolo (Electa, 2023)
The volume, published following the exhibition at the Archaeological Park of Neapolis in Siracusa, represents the originality of the research conducted by Tomás Saraceno, an Argentine artist, architect and performer, internationally known for his transversal investigations uniting architecture, art and science. Spiders and webs, the focus of the project, are one of the greatest sources of inspiration for the artist who, for the first time, used an instrument capable of measuring, scanning and digitising a spider’s web in 3D in the artistic field. Through site-specific projects, performative actions and installations, Saraceno explores the history and nature of the Sicilian archaeological site, eliciting a perpetual and constantly evolving relationship with the public, physically involved to the point of becoming part of the work. The result is an unexpected narrative about ecology and the superseding of the Anthropocene. The readers are invited to change their view of reality and connect with non-human elements such as dust, spiders and plants, presented as metaphors for the cosmos
Impressum: Il volume è stato realizzato in seguito alla mostra "Tomás Saraceno. AnarcoAracnoAnacroArcano", Siracusa, Area monumentale della Neapolis, 29 luglio 2021 - 30 gennaio 2022
Keywords: Saraceno, Tomás -- 1973-; Parco archeologico della Neapolis; Ausstellungskatalog -- Parco archeologico della Neapolis -- 29.07.2021-30.01.2022 -- Syrakus